Organizational citizenship behavior pada karyawan: Bagaimana peranan quality of work life? - Suciyanti, Novi; Sofiah, Diah; Muslikah, Etik Darul (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2025)
This study aims to examine the relationship between quality of work life and organizational citizenship behavior at PT KAI (Persero) Operational Area 8 Surabaya. The approach used in this study is quantitative with a correlational design. The research sample consisted of 108 employees selected through a simple random sampling technique. Data were collected directly using a printed questionnaire, which contained a quality of work life scale and an organizational citizenship behavior scale. Data analysis was performed using the Spearman's rho correlation technique. The results of the analysis showed that there was a significant positive relationship between quality of work life and organizational citizenship behavior with rxy = 0.515, p = 0.000 (p < 0.01). Penelitian ini bertujuan untuk mengkaji hubungan antara quality of work life dengan organizational citizenship behavior karyawan PT KAI (Persero) Daerah Operasi 8 Surabaya. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif dengan desain korelasional. Sampel penelitian berjumlah 108 karyawan yang dipilih melalui teknik simple random sampling. Data dikumpulkan secara langsung menggunakan kuesioner cetak, yang memuat skala quality of work life serta skala organizational citizenship behavior. Analisis data dilakukan dengan menggunakan teknik korelasi Spearman’s rho. Hasil analisis menunjukkan bahwa terdapat hubungan positif yang signifikan antara quality of work life dan organizational citizenship behavior dengan rxy = 0,515, p = 0,000 (p < 0,01).